Tinjauan Tentang Perlindungan Hukum Terhadap Hak-Hak Anak Akibat Perceraian dengan Alasan Salah Satu Orang Tua Pindah Agama (Studi Kasus Putusan Nomor 3/Pdt.G/2019/PTA. PAL) - Zainurrohman, Zainurrohman; Tri Budiman, Nanang; Nofitasari, Solehati (WELFARE STATE Jurnal Hukum, 2023)
In the current era, inter-religious marriages are very common among people whose obstacles are none other than legal protection, division of inheritance, child custody and so on. As has been experienced by one married couple who resides in Parigi Regency, filed a divorce divorce case and fought for custody of their children in decision Number 3/Pdt G/2019/PTA PAL. The aim of this research is to find out how the law regulates children's rights as a result of divorce on the grounds that one of the parents has changed religions based on decision Number 3 /Rev. Pdt G/2019/PTA PAL is regulated in article 3 of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. Furthermore, it is also regulated in article 105 of the Compilation of Islamic Law, the right to custody of children who are not yet mumayyiz (not yet 12 years old) was explicitly given to his mother. However, the right to child maintenance according to article 105 KHI is not an imperative provision. however, it can be set aside and ignored based on the interests of the child, this is reinforced by Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection that parents have equal and equal rights as parents are to care for, care for and care for and protect the rights of children, the most important thing is wherever parents are to care for and care for children.